Athen, Griechenland. »Copenhagen amüsiert sich, wie wohl stets, am Rand des Abgrunds. « Zwei deutsche Archäologen im Exil: Berta Segall und Willy Schwabacher im Mai 1939 - Kankeleit, Alexandra (e-Forschungsberichte des DAI, 2019)
This article offers a snapshot from 1939, shortly before the outbreak of World War Two, when two Jewish archaeologists from Germany swapped stories about their experiences in exile. Berta Segall and Willy Schwabacher became acquainted and clearly grew fond of one another while they were living and working in Greece several years earlier. After years of great uncertainty, Schwabacher landed in Denmark in spring 1939 and clearly felt at home there. His reports from Copenhagen illustrate how both archaeologists, despite precarious living conditions and frequent changes of location, remained open, creative and productive in their academic work. It becomes apparent that research and intellectual exchange functioned as anchors, providing these exiles with a firm basis for existence in turbulent times.